2018
DOI: 10.1128/mbio.02339-18
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Biofilms: a Matter of Individual Choice

Abstract: Bacillus subtilis has the capacity to choose between two mutually exclusive lifestyles: biofilm formation and flagellum-mediated swimming motility. Interestingly, this choice is made at the individual cell level, with bacterial cells in a population expressing genes required for biofilm formation or genes required for swimming motility but not both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…It has been reported that Bacillus subtilis has the capacity to choose at the individual cell level between biofilm formation and flagellum-mediated swimming motility with bacterial cells in a population expressing genes required for biofilm formation or genes required for swimming motility but not both. The decision to form either biofilm or free swimming cells by B. subtilis is mediated by a bistable switch controls called "bet hedging" that ensures that subpopulations of bacteria continue to grow as conditions change and/or become unfavorable (Ryan-Payseur and Freitag, 2018). The various processes and stages involved in biofilm formation by B. subtilis have been described (Gingichashvili et al, 2017;Ryan-Payseur and Freitag, 2018;Arnaouteli et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Bacillus subtilis has the capacity to choose at the individual cell level between biofilm formation and flagellum-mediated swimming motility with bacterial cells in a population expressing genes required for biofilm formation or genes required for swimming motility but not both. The decision to form either biofilm or free swimming cells by B. subtilis is mediated by a bistable switch controls called "bet hedging" that ensures that subpopulations of bacteria continue to grow as conditions change and/or become unfavorable (Ryan-Payseur and Freitag, 2018). The various processes and stages involved in biofilm formation by B. subtilis have been described (Gingichashvili et al, 2017;Ryan-Payseur and Freitag, 2018;Arnaouteli et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The decision to form either biofilm or free swimming cells by B. subtilis is mediated by a bistable switch controls called "bet hedging" that ensures that subpopulations of bacteria continue to grow as conditions change and/or become unfavorable (Ryan-Payseur and Freitag, 2018). The various processes and stages involved in biofilm formation by B. subtilis have been described (Gingichashvili et al, 2017;Ryan-Payseur and Freitag, 2018;Arnaouteli et al, 2021). One important attribute of biofilm that encourages their persistence is the reduced susceptibility to antimicrobials including antibiotics, disinfectants and antiseptics (Stewart, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…B. subtilis is a common soil-dwelling bacterium typically associated with plant roots, forming versatile biofilms with heterogeneous subpopulations. The subpopulations use a bet-hedging strategy to choose between either biofilm formation or flagella-mediated motility (43). In this study, we have characterized the importance of NaCl as a chemical cue and its potential influence the bistable switch that controls the biofilm (sessile) versus flagella-mediated motility decision.…”
Section: Discussionmentioning
confidence: 99%
“…formation (Ryan-Payseur & Freitag, 2018;Zhang et al, 2020). A pdeB mutant is unable to form biofilms and inactivation of the gene leads to haemolysis in L. monocytogenes.…”
Section: Collecti Ve Behaviour Of Bac I Llus Su Bti Lis Cells: Swimmi...mentioning
confidence: 99%